Design and Optimization of a Polyethylene Oxide-Based Matrix Tablet of Metoprolol Succinate Using Design Expert Software: Pharmaceutical Science-Pharmaceutics - Dighe, Pearl; Deshpande, Mangirish (International Journal of Life Science and Pharma Research, 2023)
Hypertension is a common lifestyle disorder, the prevalence of which advances with age. In the case of antihypertensive therapy, patient compliance is hampered, especially in geriatric patients, if the dose is b.i.d or more, as it is difficult for the patient to remember and take medicine at a scheduled time. The present study involves the fabrication of a sustained-release matrixdesigned tablet using a combination of polyethylene oxide (PEO) polymers and metoprolol succinate as the model drug. The tablet is optimized and evaluated for its in-vitro release using the Design expert software. Polyethylene oxide is a non-ionic hydrophilic polymer which is directly compressible. Polyox WSR 301 and 303 grades have been used in the study to get the desired sustained release of 12 h. The formulations were analysed for various pre-compression and post-compression characteristics. The polymers Polyox WSR 301 and 303 influence drug release are measured using a 32 factorial design where the concentration of drug released at various time points has been analysed statistically as a response. Response surface plots demonstrate and depict the effect of the variables, thus aiding in optimization. All the formulated batches exhibited acceptable pre and post-compression characteristics. The optimized formulation M05 showed a sustained drug release up to a 12 h period. Thus polyethylene oxide can be used as an excellent sustained-release matrix polymer due to its ability to gel and prolong drug release from a matrix. Due to their molecular weight, a combination of two grades of polyethylene oxide helps reinforce the drug release.